Asesmen Atraksi Beka’ Ecotourism Guna Peningkatan Kunjungan Wisatawan di Pulau Masakambing Sumenep - Ihsannudin Ihsannudin; sriyono sriyono; Nurul Arifiyanti (Sigmagri, 2022)
Beka' ecotorism is an ecotourism trip that offered by the Beka' Island Tourism Awareness Group (Pokdarwis) in the KEE area of ​​Masakambing Island, Sumenep Regency, East Java Province. Ecotourism which is included in special interest category propose bird watching attraction of the yellow-crested cockatoo (Cacatua sulphurea abbotti) and panoramic views of the landscape on land, coast and waters. The study aims to assess the attractions that offered by Beka' Ecotourism consists of level of attractions, ecological conditions, conditions of facilities and infrastructure and local community perceptions related to ecotourism activities. The research design uses a quantitative approach with a descriptive analysis of frequency. The research location was conducted in Masakambing Island, Masalembu District, Sumenep Regency, East Java Province. The results of the study show Beka' Ecotourism Masakambing Island has a high ecotourism attraction, especially on the jungle track mangrove attraction and bird watching of the yellow-crested cockatoo. Ecological conditions are still considered very good, especially in the mangrove spot and Karang Pote island. Facilities and infrastructure are considered good, especially from the social infrastructure in the form of the kindess of the local community. Furthermore, local community has a positive perception for ecotourism activity because it will is considered able to support improving of economic for local community. Even though it has high attractions, Beka' ecotourism in Masakambing Island is still constrained by remote location, so proper promotion efforts are needed..